Injuries Rates Are Lower in Females Comparing to Males. A Review of Injuries in 18 World Cup Tournaments - Tang, Nian; Yang, Xiaoning (Shahroud Journal of Medical Sciences, 2025)
Football, being one of the most popular sports globally, gains immense attention during FIFA world cup tournaments. However, among the spectacle and passion, player’s injuries remain a significant concern. This has an impact on footballers of both genders. In addition, has been reported that the rate of injury in senior elite athletes women´s football is lower than found in elite male football. This study aims to estimate the incidence of injury in elite senior football during world cup matches as well as to identify the nature of the injury in world cup tournaments. We used FIFA medical reports and previous scientific studies for data extraction. Using t-test for statistical analysis, we found higher total injury incidence (P-value=0.014), higher injury per match of males than females (P-value<0.01), and higher rates of non-contact injuries on males than females (P-value<0.01), in world cup tournaments. Understanding the landscape of football injuries in world cup tournaments is crucial for strategy prevention, enhancing player safety and optimizing performance. The study also highlights the significant gender differences in injury epidemiology, underscoring the need for tailored injury prevention strategies and training protocols for each gender.